-6(2r+8)=2(x-10)

Simple and best practice solution for -6(2r+8)=2(x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2r+8)=2(x-10) equation:


Simplifying
-6(2r + 8) = 2(x + -10)

Reorder the terms:
-6(8 + 2r) = 2(x + -10)
(8 * -6 + 2r * -6) = 2(x + -10)
(-48 + -12r) = 2(x + -10)

Reorder the terms:
-48 + -12r = 2(-10 + x)
-48 + -12r = (-10 * 2 + x * 2)
-48 + -12r = (-20 + 2x)

Solving
-48 + -12r = -20 + 2x

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + -12r = -20 + 48 + 2x

Combine like terms: -48 + 48 = 0
0 + -12r = -20 + 48 + 2x
-12r = -20 + 48 + 2x

Combine like terms: -20 + 48 = 28
-12r = 28 + 2x

Divide each side by '-12'.
r = -2.333333333 + -0.1666666667x

Simplifying
r = -2.333333333 + -0.1666666667x

See similar equations:

| 150*x+2500=175*x+1700 | | 65=(3-l)w | | 6m-2+m^2+3=56 | | r=3(9t-4) | | 5(3x-4)-3x-2=4 | | 5p-12+2p=6+3p-11 | | n^2+7n-18=0 | | 6(3-2x)+8x=9 | | (5y+4)(y+6)=-4(5y+4) | | -1=5x^2-9x+2 | | 2n-12=53 | | -96+2x=-8x+34 | | 108x^2+63xy+9y^2= | | c(q)6000+10qR(q)=12q | | 8x-9(x+1)=3(5-x) | | d=3e | | 8x=5x+4+5 | | C(q)=600+10q | | x^4-31x^2-180=0 | | 2x+9x-2=33 | | -y+6+3y=-5+y | | -12=-2h+.2(20-6h) | | 5x-71=x+41 | | 4p+21=11p | | 3x+6x-4=4-6 | | 3(2x+1)+4x=43 | | -x-2x-4=3 | | x-4*2x=240 | | 15-(3-4x)=2(y+2) | | (2x-4)x=240 | | 6x^2+3=5x | | x^2-10x-18=0 |

Equations solver categories